THE RELATIONSHIP BETWEEN JOB CRAFTING AND WORK LIFE BALANCE IN CIVIL SERVANT TEACHERS AT SMA NEGERI 1 LUBUK ALUNG - Ningsih, Meysy Novia; Pratama, Mario (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
The purpose of this study is to see if there is a relationship between job crafting and work-life balance in civil servant teachers at SMA Negeri 1 Lubuk Alung. This research is quantitative with a correlational approach. The subjects of this study are 44 civil servant teachers at SMA Negeri 1 Lubuk Alung. The data of this study was collected using a likert scale consisting of two scales, namely the work life balance scale and the job crafting scale. The research sampling technique is using total sampling.The data analysis method used in this study is Pearson's Product Moment method. The results of the study showed that there was a positive relationship between job crafting and work-life balance in civil servant teachers at SMA Negeri 1 Lubuk Alung. The correlation test produced a correlation coefficient of 0.403 and a significance level of 0.007. Job crafting contributes 16.3% to the work-life balance of civil servant teachers at SMA Negeri 1 Lubuk Alung.